2013
DOI: 10.1063/1.4813272
|View full text |Cite
|
Sign up to set email alerts
|

Defect states in hybrid solar cells consisting of Sb2S3 quantum dots and TiO2 nanoparticles

Abstract: We have studied defect states in an organic-inorganic hybrid solar cell containing Sb2S3 quantum dots (QDs) and TiO2 nanoparticles (NPs) by using deep level transient spectroscopy (DLTS). An Au electrode was deposited as a Schottky contact on the sample, where the Sb2S3 QDs were distributed on the surface of TiO2 NPs by chemical synthesis. The activation energy and capture-cross section of an interface state between the Sb2S3 QDs and the TiO2 NPs were found to be about 0.78 eV and 2.21 × 10−9 cm−2, respectivel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 31 publications
0
17
0
Order By: Relevance
“…The typical crystallization temperature is 300 °C [2,6,29,31,37] while values of 330 °C [45 32,50] and up to 400 °C [51] are reported. To gain insights into the crystallization behavior in terms of morphology, creation of defects and solar cell performance we produced samples crystallized on a hot plate at various temperatures in a nitrogen atmosphere.…”
Section: Resultsmentioning
confidence: 99%
“…The typical crystallization temperature is 300 °C [2,6,29,31,37] while values of 330 °C [45 32,50] and up to 400 °C [51] are reported. To gain insights into the crystallization behavior in terms of morphology, creation of defects and solar cell performance we produced samples crystallized on a hot plate at various temperatures in a nitrogen atmosphere.…”
Section: Resultsmentioning
confidence: 99%
“…An absorber bandgap of 1.65 eV is found in solar cells with Sb 2 S 3 prepared by ALD [5,19] or in solar cells with Sb 2 S 3 prepared by CBD, as estimated from the photocurrent edge at around 750 nm in the published EQE plots [2,4,69 1112 1517 4041 5053]. Any E g larger than 1.7 eV up to 2.6 eV have been attributed to nanocrystalline Sb 2 S 3 [1,44,54], or to amorphous Sb 2 S 3 [6,4445 53], while it is also known that contamination, most notably with oxygen, can significantly increase the bandgap value of metal sulfide films [23,5556]. Values of 1.52–1.55 eV are reported for layers of nanotubes, -rods, or -flakes that consist of single phase Sb 2 S 3 [5759].…”
Section: Resultsmentioning
confidence: 99%
“…The present paper relies on the recently proven concept of TiO 2 /Sb 2 S 3 /P3HT solar cells [112], in which Sb 2 S 3 is the light absorber, also called the sensitizer, situated in the electrical junction created by TiO 2 and P3HT (polythiophene) as the electron and hole conductor, respectively. For these type of solar cells, fluorine doped tin oxide (FTO) is prevalently used to contact the TiO 2 while evaporated Au has been used to contact the P3HT.…”
Section: Introductionmentioning
confidence: 99%
“…Because of the large surface area in SSCs, the performance will be limited primarily by interface defects, which in some studies was found to be on the order of 10 11 -10 12 cm À2 at the TiO 2 -mp/Sb 2 S 3 -nc interface. 110 On the other hand, Darga et al argued that dominant recombination events in TiO 2 /Sb 2 S 3 with flat geometry stems from the bulk Sb 2 S 3 . 93 Additionally, according to the temperature-dependent electrical conductivity measurements of thin Sb 2 S 3 films, the determined activation energy was in the 0.5-0.9 eV range, 67,111,112 the Fermi level was found to be pinned at near midgap, 67 and high activation energy was calculated by DLTS, 90 all strongly suggesting the existence of deep traps.…”
Section: Sb 2 S 3 -Based Photovoltaic Device Limitationsmentioning
confidence: 99%